Loose Verses, Commonplaces, Found Poems [Versos Sueltos, Lugares Comunes, Poemas Encontrados] - Cussen-Abud, F (2013)
In this article I analyze three poems by Nicanor Parra, whose structure is based on the accumulation of apparently not poetic elements: "Versos sueltos", "Ideas sueltas" and "Frases". From these procedures, I establish relationships with the Renaissance poet François Villon, and some contemporary tendenciess such as found poems and conceptual poetry.